Perancangan Sistem Penentuan Lead Time Produksi Berdasarkan Kapasitas dan Waktu Baku pada PT. X - Kevin Kusuma Prawiro; Prayonne Adi (Jurnal Titra, 2021)
PT. X is a subsidiary of PT Astra Otoparts engaged in the automotive industry in producing motorcycle chains, engine chains, filters, and accessories for motorbikes. PT. X has 2 customer chain products, namely OEM (Original Equipment Market) products which include Astra Honda Motor (AHM), Yamaha, Kawasaki, and Suzuki. RM Products (Replacement Market) which include Honda Genuine Part (HGP) and Yamaha Genuine Part (YGP). The chain of OEM products is a chain that will be installed directly on a motorcycle during the assembly process. The RM product chain is a spare parts chain that will be marketed in motorcycle dealers. Determining the standard time and production capacity of each process aims to determine the production lead time. Production lead time is needed by the company to determine a product from the start of the raw material being processed to the end of being a chain product. The results of the calculation of the standard time of each process can be analyzed as the cause of the delay in product distribution to the customer. The results of this study are used to determine the production lead time for a certain period with the number of stock components, the number of chain stocks used for production plans for a certain period. The production plan uses data from the calculation of the standard process time and process capacity used to determine the production lead time.